P05.10 Antimicrobial resistance of neisseria gonorrhoea in germany, results from the gonococcal resistance network (gorenet). (13th September 2015) - Dudareva-Vizule, S; Buder, S; Jansen, K; Loenenbach, A; Nikisins, S; Sailer, A; Guhl, E; Kohl, PK; Bremer, V
Abstract : Introduction: Neisseria gonorrhoeae (NG)-infections are not reportable in Germany and only limited data on NG-epidemiology and antimicrobial resistance (AMR) are available. With GORENET we monitor the NG-AMR and patterns of resistance testing in Germany in order to guide treatment algorithms and targeted prevention strategies. Methods: We recruited laboratories based on geographic distribution and number of NG-isolates. From April 2014 prospective data on all performed NG-AMR-tests together with patient-related information were collected. Laboratories send a part of the isolates to the national reference laboratory (NRL) for culturing and AMR-testing towards ceftriaxone, cefixime, azithromycin, ciprofloxacin, and penicillin by using E-Test, as well as beta-lactamase. Results are interpreted according to European Committee on Antimicrobial Susceptibility Testing 4.0. We described the reported samples by sex and age and characterised isolates tested in NRL by resistance patterns. We calculated proportions and medians, together with interquartile range (IQR), where appropriate. Results: Between April and December 2014 we received information on 651 isolates tested in 19 laboratories. Altogether, 90.3% isolates were from men and 8.5% from women. Median age of tested men was 36 (IQR 29–49) and women 28 (IQR 22–41) years. NRL received 502 isolates, 342 were vital and 253 were tested for AMR. From those 0 were resistant towards ceftriaxone, 1.6% towards cefixime, 11.1% towards azithromycin, 73.1% towards ciprofloxacin, and 30.4% towards penicillin. Further 37.9% and 50.6% isolates were intermediate susceptible to Azithromycin and to Penicillin. From 205 isolates tested for beta-lactamase, 25.9% were positive. Conclusion: In Germany isolates tested for NG-AMR were mostly from men. We assume that a substantial proportion of these isolates could be from men having sex with men. NG-AMR to ceftriaxone and cefixime remains low, while resistance and intermediate susceptibility to azithromycin, ciprofloxacin and penicillin is substantial. Monitoring of NG-AMR should be highly prioritised. Disclosure of interest statement: The GORENET Project is funded by German Federal Ministry of Health. No conflicts of interest.